Battery Rental Scheme for Increasing the Adoption of Four Wheeled Electric Vehicles: A Conjoint Analysis - Donovan, Andreas Arga; Windasari, Nila A. (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
The study explores key factors influencing consumer preferences for battery rental schemes and their role in increasing four-wheeled electric vehicle adoption in Indonesia. Using the Theory of Planned Behavior (TPB) and Technology Acceptance Model (TAM), data was gathered via an online survey targeting potential EV buyers in the Jakarta metropolitan area. The goal was to identify the most appealing rental scheme based on consumer priorities like affordability, convenience, and reliability. Findings reveal that rental cost holds the greatest weight (40 percent), followed by battery warranty (30 percent), after-sales service (20 percent), and replacement cost (10 percent). Among tested options, scenario 3 with IDR 800,000 monthly rental, lifetime warranty, free replacement, and full after-sales support was most preferred, capturing 35 percent projected market share.